Faktor–Faktor yang Berhubungan dengan Kenyamanan, Beban Gejala, dan Depresi pada Pasien Kanker Payudara - Mustafidz, Mustafidz; Nuraini, Tuti; Hargiana, Giur; Gayatri, Dewi (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate factors associated with comfort, symptom burden, and depression in breast cancer patients. The method used was a systematic review following PRISMA guidelines, with searches in PubMed, Embase, and ScienceDirect until March 2024 using the terms "breast cancer," "comfort," "symptom burden," and "depression." Research results from 9 articles show that demographic factors, clinical factors, and psychological factors have an impact on patient comfort. Symptom burden was influenced by race, age, employment status, and place of residence. At the same time, bisphosphonate treatment, metastasis, comorbidities, disease stage, chemotherapy, hormone therapy, and physical activity contributed to variation in symptom burden. Depression, as measured, was also analyzed, as well as these factors. In conclusion, comfort, symptom burden, and depression in breast cancer patients are influenced by various demographic, clinical, and psychological factors. Keywords: Symptom Burden, Depression, Breast Cancer, Comfort